Protocol of patient's initial valuation at the admitted to nursing care unit - Josefa Moral Jiménez; Mª África Conde Anguita; Eduardo Mesa Fernández (Fundación para el Desarrollo de la Enfermería, 2010)
The initial valuation of a patient, when he is admitted to Nursing Care Unit, is an essential tool to identify the necessities of the patient and to make the nursing diagnostics so it is the starting point to do a good medical care's plan. In this unit the patient's valuation is only complete after interviewing the main health caretaker.For this reason we need to have a protocol which allows the professional to have uniformity of criterion in order to assure a perfect coordination of interventions and a good continuity of cares.The initial valuation document, as a nursing registration, is part of the clinical history of the patient. These registrations allow the nursing work to be valued.